Effect of hydrotherapy on recovery from fatigue - Vaile, J.; Halson, S.; Gill, N.; Dawson, B. (International Journal of Sports Medicine, 2008)
The present study investigated the effects of three hydrotherapy interventions on next day performance recovery following strenuous training. Twelve cyclists completed four experimental trials differing only in 14-min recovery intervention: cold water immersion (CWI), hot water immersion (HWI), contrast water therapy (CWT), or passive recovery (PAS). Each trial comprised five consecutive exercise days of 105-min duration, including 66 maximal effort sprints. Additionally, subjects performed a total of 9-min sustained effort (time trial - TT). After completing each exercise session, athletes performed one of four recovery interventions (randomly assigned to each trial). Performance (average power), core temperature, heart rate (HR), and rating of perceived exertion (RPE) were recorded throughout each session. Sprint (0.1 - 2.2 %) and TT (0.0 - 1.7 %) performance were enhanced across the five-day trial following CWI and CWT, when compared to HWI and PAS. Additionally, differences in rectal temperature were observed between interventions immediately and 15-min post-recovery; however, no significant differences were observed in HR or RPE regardless of day of trial/intervention. Overall, CWI and CWT appear to improve recovery from high-intensity cycling when compared to HWI and PAS, with athletes better able to maintain performance across a five-day period.